Immune protection induced by E2 recombinant glycoprotein of bovine viral diarrhea virus in a murine model - Gómez-Romero, Ninnet; Arias, Carlos F.; Verdugo-Rodríguez, Antonio; López, Susana; Valenzuela-Moreno, Luis Fernando; Cedillo-Peláez, Carlos; Basurto-Alcántara, Francisco Javier (Frontiers in Veterinary Science, 2023)
Bovine viral diarrhea virus (BVDV) is considered the most important viral pathogen in ruminants worldwide due to the broad range of clinical manifestations displayed by infected animals. Therefore, infection with BVDV leads to severe economic losses in several countries' beef and dairy industries. Vaccination prevents reproductive failure and gastrointestinal and respiratory disorders caused by BVDV infection. However, considering their limitations, conventional vaccines such as live, attenuated, and killed viruses have been applied. Hence, different studies have described subunit vaccines as an effective and safe alternative for BVDV protection. Therefore, in this study, the ectodomain of E2 (E2e) glycoprotein from NADL BVDV strain was expressed in mammalian cells and used in two vaccine formulations to evaluate immunogenicity and protection against BVDV conferred in a murine model. Formulations consisted of solo E2e glycoprotein and E2e glycoprotein emulsified in adjuvant ISA 61 VG. Five groups of 6 mice were immunized thrice on days 1, 15, and 30 by intraperitoneal injection with the mentioned formulations and controls. To evaluate the conferred protection against BVDV, mice were challenged six weeks after the third immunization. In addition, the humoral immune response was evaluated after vaccination and challenge. Mice groups inoculated with solo E2e and the E2e + ISA 61 VG displayed neutralizing titers; however, the E2 antibody titers in the E2e + ISA 61 VG group were significantly higher than the mice group immunized with the solo E2e glycoprotein. In addition, immunization using E2e + ISA 61 VG prevent animals from developing severe lesions in surveyed tissues. Moreover, this group acquired protection against the BVDV challenge, evidenced by a significant reduction of positive staining for BVDV antigen in the lungs, liver, and brain between the experimental groups. Our findings demonstrated that using E2e + ISA 61 VG induces greater BVDV protection by an early humoral response and reduced histopathological lesions and BVDV antigen detection in affected organs, indicating that E2e + ISA 61 VG subunit formulation can be considered as a putative vaccine candidate against BVDV.